Broilers Serum Cholesterol and Glutamic Oxaloacetic Transaminase and Their Relation to Antibiotic in Feed and Medication Programs in Four Broiler Producers in Semarang Region-Central Java, Indonesia - Murwani, R.; Bayuardhi, B. (International Journal of Poultry Science, 2007)
This study was carried out to investigate the use of antibiotic in feed and medication programs and their effects on broilers Serum Cholesterol and Glutamic Oxaloacetic Transaminase (SGOT). The broilers were sampled randomly from four small-scale broiler producers (BP1, BP2, BP3, BP4) in Semarang region-Central Java, Indonesia. Observed data comprising medication programs and the types of feed ingredients in the commercial complete feed were obtained from medication program brochures and feed labels respectively. Four unsexed broilers from each poultry producer were randomly sampled at selling point in poultry slaughterhouse. Broilers market body weight and abdominal fat percentage were measured on the spot. Blood was taken to obtain the serum samples for determination of serum cholesterol and SGOT. An independent experimental study (E1) was also carried out approximately the same time as the field study using the same feed as in BP-4 and raised under similar condition as in the broiler producers. However, no medication program was employed. The results showed that all feeds from four different feed companies (FC1, FC2, FC3, FC4) used by the four BPs respectively contained antibiotics. Antibiotics were also administered in medication program via drinking water. The market age was found to be 34-35 days old and market weight was in average 1760.38±54.14 g with no significant difference among producers. This market weight had no significant difference to E1. There was no significant difference in broilers abdominal fat percentage and SGOT among BPs. However, these abdominal fat and SGOT were significantly higher than E1. There is a significant difference in serum cholesterol of broilers among BPs, where BP-4 had the highest (145.2±6.59 mg dl-1) and BP-3 had the lowest serum cholesterol level (117.53±9.76 mg dl-1). These serum cholesterol and SGOT levels were significantly higher than those in E1 or in those published results that used in-feed antibiotic and no-medication (E2) or no antibiotic in feed nor medication (E3). These results suggested that antibiotic in feed and medication program affect lipid and hepatic metabolism of broilers which is reflected by an increase in serum cholesterol and SGOT.